Utilization of Learning Materials in Teaching Listening Skills: Content Analysis and Teacher’s Experience - Nurul Fitri; Yanty Wirza (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
Listening is the most frequently used yet least systematically taught language skill in Indonesian junior high school. The quality of the learning materials that mediate it remains under-examined. This study analyses the listening materials used by a teacher in an Indonesian junior high school and investigates how that teacher utilizes and adapts them in practice. Adopting a qualitative design that combines directed content analysis with a single-teacher case study, the research evaluated an elementary coursebook together with teacher-supplemented tasks, using Cunningsworth’s (1995) coursebook-evaluation checklist as the analytical instrument. Data on teacher experience were gathered through a semi-structured interview. The content analysis revealed that the materials offer a strong variety of listening text types and largely contextualized, level-appropriate audio, but are weak in authenticity, visual exploitation, and local cultural relevance, while tasks are dominated by listening for specific detail at the expense of the gist and inferential listening. The teacher’s account confirmed these patterns and showed deliberate supplementation to compensate for coverage gaps. The study offers practical recommendations for selecting and adapting listening materials in resource-constrained EFL settings.